Administrasi Desa dalam Menunjang Efektivitas Kinerja di Gampong Kuala Tuha - Sri Wahyu Handayani (Universitas Teuku Umar, 2019)
Government administration plays an important role in the smooth running of village government affairs because the involvement of the gampong government in the administration system is very much needed. With this in order that the objectives of the village government can actually be achieved as expected, then what needs to be considered is that government officials who have the quality or ability must be adequate. In order to carry out village administration effectively, it is necessary to provide guidance and supervision carried out by the sub-district government on the village government apparatus, especially in the field of government. For this purpose, village officials can carry out their duties and obligations properly in serving and administering administration in the community. The existence of the village government is a tool to achieve national development goals and as an organization that strengthens the governance structure of the Indonesian state. The implementation of the gampong kuala tuha government has been running for four years, but in its implementation there are still a number of things that need to be considered by the Village Government. This research uses approach approaching training activities that are organized using practical methods, training and discussion, from the results of this study the researchers concluded that the Government in the village of kuala tuha has not been able to regulate or organize village administration properly and effectively.